Prädiktive PD-L1-Immunhistochemie beim nichtkleinzelligen Bronchialkarzinom: aktueller Stand und Erfahrungen der ersten deutschen Harmonisierungsstudie = Predictive PD-L1 immunohistochemistry for non-small cell lung cancer : current state of the art and experiences of the first German harmonization study - Scheel, Andreas; Schirmacher, Peter; Warth, Arne (Der Pathologe, 2016)
BackgroundAntibodies against PD-1 and PD-L1 can cause strong and durable anti-tumor immune responses in non-small cell lung cancer (NSCLC). Immunohistochemistry for PD-L1 (PD-L1 IHC) was tested as a predictive biomarker. Several IHC assays and interpretation criteria were developed in parallel.AimThe clinical significance of PD-L1 IHC in NSCLC and the optimum method for staining and interpretation of the results are the subject of ongoing studies. The diagnostic application of immunotherapy in NSCLC necessitates harmonization of PD-L1 IHC to obtain evidence for guidelines; therefore, a consensus opinion on a well-founded diagnostic mode of testing should be defined based on published studies and the results of the first German PD-L1 IHC harmonization study.Methods1. Summary of the current data situation. 2. Evaluation of the first German PD-L1 IHC harmonization study (centralized, staining with PD-L1 IHC analogous to studies, 15 cases of NSCLC, 4 IHC study assays [28‑8, 22C3, SP142 and SP263] and scoring by 9 pathologists).ResultsThe use of PD-L1 IHC in NSCLC is suitable for identification of patients with an increased probability of a clinical benefit from immunotherapy. The various proportional cut-offs used to interpret the staining results can be summarized in a total score, which can be reproducibly assessed. The staining patterns of the four assays investigated were, however, not congruent in all situations.DiscussionIn principle, the use of PD-L1 IHC for assessment of the expression in tumor cells is a reliably determinable biomarker. Evaluation algorithms should be based on published clinical trials. For NSCLC approvals with obligatory PD-L1 IHC are to be expected but it remains to be seen to what extent PD-L1 IHC will be implemented in the clinical routine.